Impact of Translation on the Comparability of Financial Reports - Mejzlik, Ladislav; Roe, Jana (Видавництво Львівської політехніки, 2011)
International financial reporting standards (IFRS) aim to provide unified guidance that would result in increased global comparability of financial reports. Because IFRS is written in English and subsequently translated to other languages, cultural differenes give rise to high potential for mistranslation and miscommunication when translating and interpreting standards and reports. Crucial for successful translation is the translator’s understanding of not only technical terminology but also the underlying concepts.
Keywords: IFRS; translation; financial reporting; cultural differences; globalization; convergence